Les joints de grains : de la théorie à l'ingénierie - Priester, Louisette (Collection Matériaux. Métallurgie., 2006)
This work deals with homophase interfaces in crystalline materials. It is addressed to Ph.D. students, engineers and young researchers in the science of materials.